Exploring Geometric Concepts in the Medan Post Office through an Ethnomathematical Approach - May Sharah Athifah; Tanti Jumaisyaroh (MASI Mandiri Edukasi, 2026)
Geometry is often considered abstract and difficult to understand because it is rarely linked to real life and the surrounding culture. Therefore, a learning innovation is needed using the Medan Post Office. A culturally acculturated colonial heritage building studied in depth from an ethnomathematical perspective. This study aims to explore the cultural values ​​and geometric concepts inherent in the architecture of the Medan Post Office using an ethnomathematical approach. It employs a qualitative ethnographic design, utilizing primary data from observations and interviews alongside secondary data from relevant literature; data analysis was conducted through reduction, presentation, and conclusion drawing. The findings reveal concepts of plane geometry (rectangles, squares, circles, semicircles, octagons, right-angled trapezoids, and isosceles triangles) and spatial geometry (pyramids, prisms, rectangular prisms, and cubes). The building embodies ethnomathematical elements resulting from the acculturation of local culture with colonial architecture, socio-historical functions, and environmental adaptation. This research enriches the study of cultural heritage ethnomathematics and offers potential as a resource for contextual, culture-based mathematics learning.